Agreement of Urine Sediment Using Shih-Yung Method in Aspirated and Decanted Supernatant Removal Technique - Jesi Anggraini; Rikarni Rikarni (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
The technique of supernatant removal in urine sediment examination using the Shih-Yung method can be done by aspirating and decanting. The aspirated technique is the recommended technique. The Central Laboratory Installation of Dr. M. Djamil Hospital, Padang used decanted supernatant removal technique. The variety of preanalytical procedures affect the results of urine sediment examination. This study aimed to analyze the agreement of erythrocyte, leukocyte, and non-hyaline cast sediment examination results using the Shih-Yung method in aspirated and decanted supernatant removal technique. This study was an analytical observational study with a cross-sectional design of 37 urine specimens that met the inclusion and exclusion criteria at the Central Laboratory Installation of Dr. M. Djamil Hospital, Padang from July to September 2020. Examination of erythrocyte, leukocyte, and non-hyaline cast sediment using Shih-Yung method with aspirated and decanted supernatant removal technique. Numeric data were analyzed using the Mann-Whitney U test and Cohen's Kappa test for the degree of agreement, p-value < 0.05 was considered significant. The agreement test results for erythrocyte, leukocyte, and non-hyaline cast sediment in aspirated and decanted supernatant removal technique were (Kappa=0.88, p < 0.05), (Kappa=0.83, p < 0.05), and (Kappa=0.86, p < 0.05), respectively. The degree of agreement test results for erythrocyte, leukocyte, and non-hyaline cast sediment using the Shih-Yung method in aspirated and decanted supernatant removal technique were almost perfect and statistically significant. The technique for supernatant removal in urine sediment examination using the Shih-Yung method can be done by decanting.